DEVELOPING VOTER COMMITMENT THROUGH MUNICIPAL SERVICE QUALITY IN LOCAL POLITICS: SAMPLE OF TRB-1 REGION - Erkan Turan DEMİREL (Fırat University, 2019)
Public services provide contribution to development, democracy, public peace and wealth more than private sector. Municipal services have a special place within public services. Democracy and peace of society would be powerful in general sense much as in local sense. Then, first of all quality criteria should be acquired in local services then leave this situation to protection. Quality criteria to be acquired are the criteria determined by citizens who are the users of municipal services. In this sense, it is expected that citizens will/should be sensitive towards the quality of municipal services. Municipalities which are administered by mayor presenting qualified service and inspire (standing as a model) voters would consolidate the belief towards local democracy and form mass of voters who has strong sense of commitment. The main aim of this study which was formed within the frame of views mentioned above is “to determine decisiveness of service quality of municipalities on voters commitment that can be formed by mayor”. Quantitative research method was chosen in order to fulfill the aim of study. Since decisiveness of variables over each other was the focus point in the study, the study was carried out according to correlation research method within the scope of quantitative research. The population of study was composed of voters living within city center municipalities in TRB1 region. Total number of voters in the mentioned cities is 554.618 according to data of 31.12.2009. 1616 voters were accessed randomly within mentioned population and data were collected through survey form. There are scales (quality of municipal services, voters loyalty) developed by researchers and questions concerning with demographical characteristics were included in the survey. As a result; there was a significant, strong and positive correlation between quality of municipal services and voters commitment.